Expression of a functional VEGFR-1 in tumor cells is a major determinant of anti-PlGF antibodies efficacy - Yao, Jenny (National Academy of Sciences, 2011)
PlGF, one of the ligands for VEGFR-1, has been implicated in tumor angiogenesis. However, more recent studies indicate that genetic or pharmacological inhibition of PlGF signaling does not result in reduction of microvascular density in a variety of tumor models. Here we screened 12 human tumor cell lines and identified 3 that are growth inhibited by anti-PlGF antibodies in vivo. We found that efficacy of anti-PlGF treatment strongly correlates with VEGFR-1 expression in tumor cells, but not with antiangiogenesis. In addition, PlGF induced VEGFR-1 signaling and biological responses in tumor cell lines sensitive to anti-PlGF, but not in refractory tumor cell lines or in endothelial cells. Also, genetic ablation of VEGFR-1 signaling in the host did not affect the efficacy of PlGF blockade. Collectively, these findings suggest that the role of PlGF in tumorigenesis largely consists of promoting autocrine/paracrine growth of tumor cells expressing a functional VEGFR-1 rather than stimulation of angiogenesis.